Johan Nicolai Madvigs dannelsestanker (Vol. 337):En kritisk humanist i den danske romantik - Jesper Eckhardt Larsen (Studier fra Sprog- og Oldtidsforskning, 2006)
() encircles the notion of education which has influenced the self-perception of the Danish elite up to the present day. Madvig (1804-1886) has occupied a special position in Danish educational tradition since he in the 1830s formulated an independent suggestion for a cultural education, which proved extremely influential in the development of the learned school in the second half of the 19th century. Jesper Eckhardt Larsen has an MA in History from the University of Copenhagen.